Pedagogical Competence as the Key Driver: Analyzing the Relative Impact on Mathematics Achievement in Primary School - Handriani, Handriani; Firdaus, Fery Muhamad; Alifah, Khairunnisa Zulfa (Jurnal Penelitian Ilmu Pendidikan, 2025)
While teacher competence is widely acknowledged as crucial for student success, the relative importance of its specific dimensions—pedagogical versus professional competence—remains less clear, particularly in specific local contexts of primary mathematics education. This correlational study investigated the distinct impacts of these two competencies on the mathematics achievement of 45 sixth-grade students at SD Negeri 7 Buntok, Indonesia. Data were collected through a validated teacher competency questionnaire (completed by 3 class teachers) and a curriculum-based mathematics test. Multiple linear regression analysis revealed that both competencies significantly predicted student achievement, jointly explaining 54.1% of the variance in scores. Notably, pedagogical competence (β = 0.59, p = 0.001) emerged as a stronger unique predictor than professional competence (β = 0.38, p = 0.010). These findings underscore that while deep content knowledge is necessary, the ability to design, deliver, and manage effective instruction is paramount for enhancing student learning outcomes. The study provides empirical evidence for prioritizing pedagogical skill development in teacher training and professional development programs to improve primary mathematics education.